An integrated fuzzy DEMATEL-fuzzy ANP model for evaluating construction projects by considering interrelationships among risk factors - Hatefi, Seyed Morteza; Tamošaitienė, Jolanta (Journal of Civil Engineering and Management, 2019)
Construction projects are associated with a number of uncertainties due to their expanse, complex nature, uniqueness, and dynamic states. Risks in construction projects are, indeed, the events or uncertain situations that can have negative or positive consequences on the project objectives. Many of the risks inherent in construction projects affect each other. For example, the time risk in construction projects can affect the cost risk and vice versa. The intertwined relations between risk factors are ignored in the traditional construction risk assessment methods. To fulfill this gap, this paper proposes an integrated fuzzy DEMATEL-fuzzy ANP model to evaluate construction projects and their overall risks by considering intertwined relations among risk factors. Fuzzy DEMATEL is used to determine the interrelationships and interdependencies among risk factors. The network structure for implementing the fuzzy ANP method is extracted based on the results of fuzzy DEMATEL. The fuzzy ANP is applied to assess the relative importance of risk factors and alternatives and prioritize construction projects. The proposed integrated model is used to evaluate five construction projects based on risk factors in Isfahan, Iran. The results of applying the integrated model reveal that the time, cost and safety risks with the weight values of 0.056, 0.038, and 0.034 are the most important factors among construction risks, respectively. The results reveal that the proposed model can help managers to evaluate the overall risks of construction projects, and select the best project that has the lowest risk.